1972
DOI: 10.1071/ar9720321
|View full text |Cite
|
Sign up to set email alerts
|

Digestion of two legumes and rumen bacterial growth in defaunated sheep

Abstract: Defaunated sheep offered lucerne hay or dried red clover were used to study digestion in the stomach of dietary organic matter, plant cell wall constituents, and plant cell contents. Digestion in that section of the tract was, for dietary organic matter, 50 % with lucerne and 60% with red clover, for plant cell contents 65–70% with both diets, and for plant cell wall constituents 30% with lucerne and 60 % with red clover. Estimates of growth of rumen bacteria in these sheep indicated that about 32 g of bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
23
0
3

Year Published

1973
1973
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(32 citation statements)
references
References 0 publications
6
23
0
3
Order By: Relevance
“…The decreased OM digestibility in the whole tract, observed in the present study as a result of defamation, is consistent with the findings of Klopfenstein et al (1966) and Lindsay & Hogan (1972). It appears therefore that while the rate of cellulose degradation in the rumen may actually be increased (Kurihara et al 1978) and total VFA production unchanged (present study) by defaunation, the availability of energy to the animal may be decreased.…”
Section: Defamation Rumen Fermentation and Digestion 117supporting
confidence: 82%
“…The decreased OM digestibility in the whole tract, observed in the present study as a result of defamation, is consistent with the findings of Klopfenstein et al (1966) and Lindsay & Hogan (1972). It appears therefore that while the rate of cellulose degradation in the rumen may actually be increased (Kurihara et al 1978) and total VFA production unchanged (present study) by defaunation, the availability of energy to the animal may be decreased.…”
Section: Defamation Rumen Fermentation and Digestion 117supporting
confidence: 82%
“…In addition the engulfment of bacteria by protozoa is likely to reduce further microbial amino acid availability. This study suggests that the 16% increase in protein availability on defamation of sheep observed by Lindsay & Hogan (1972) is likely to be much higher whenever protozoa numbers reach levels similar to those present in the sheep used in the present studies. The suggestion made here of only a small proportion of protozoa present in the rumen moving into the lower digestive tract is well supported by the studies of Dawson et al (1981) who showed that little or no labelling occurs in the blood lipids when sheep are fed on…”
Section: Discussionmentioning
confidence: 72%
“…Part of the apparent inefficiency in microbial cell growth, and therefore availability of microbial protein to the animal, may be attributable to the turnover ofmicrobial cells in the rumen (Nolan & Leng, 1972). The apparent retention of protozoa in the rumen (Weller & Pilgrim, 1974;Minor et al 1977;Bird et al 1978;Harrison et al 1979) and the increased microbial protein flow to the duodenum on defamation of sheep (Lindsay & Hogan, 1972), together with observation of significant quantitative engulfment of bacteria by protozoa (Coleman, 1975), all suggest that a large population of protozoa may lead to a low rate of microbial protein synthesis or flow-rate to the small intestines or both. In addition recent studies of microbial growth in ruminal digesta in vitro have indicated that the presence of protozoa increased the turnover of bacterial cells and this lowered the net yield of microbial protein (Demeyer & Van Nevel, 1979).…”
mentioning
confidence: 99%
“…With forage diets the amount of energy supplied to the rumen micro-organisms is a major factor limiting their growth, some 15-25 g of bacterial protein being synthesised per 100 g of plant organic matter fermented in the rumen (Hogan & Weston 1967, 1971Lindsay & Hogan 1972). Rumen bacteria contain approximately 2.1 g SAA-N per lOOg total N (Hogan & Weston 1971), and the apparent digestibility of this fraction in the intestines of the sheep is approximately 70% (Bird 1972).…”
Section: Factors Affecting the Sulphur (And Cystine) Content Of Wool mentioning
confidence: 99%